The verb and the paragraph in biblical Hebrew: a cognitive-linguistic approach - Robar, Elizabeth (Studies in Semitic languages and linguistics, 2014)
In this book, Elizabeth Robar demonstrates how biblical Hebrew verbal patterns can reveal paragraph structure and themes.